Analisis Belanja Modal Pemerintah dan Pendapatan Asli Daerah (PAD) Terhadap Pertumbuhan Ekonomi di Kota Jayapura - Waspada Meliala; Dhefut Riansyah Firman Ardian; Virgilio Cancera Meliala (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to determine: 1) the effect of Jayapura City Government's Locally Generated Revenue (PAD) on economic growth in Jayapura City from 2012 to 2024; 2) the effect of Jayapura City Government's Capital Expenditure on economic growth from 2012 to 2022; and 3) the contribution of capital expenditure and PAD to Jayapura City's economic growth to understand the factors influencing regional economic development. The study was conducted at the Jayapura City Government using secondary data in the form of Capital Expenditure and Locally Generated Revenue from 2013 to 2023. The population in this study was the Jayapura City Government. The research method used a quantitative approach. Data analysis techniques used multiple linear regression. The results show that 1) Locally Generated Revenue has a positive effect on economic growth in Jayapura City; 2) Capital expenditure has a positive effect on economic growth in Jayapura City; and 3) Locally Generated Revenue and capital expenditure have a positive effect on economic growth in Jayapura City, expressed as a 10.38 percent increase if held constant.